Design and Validation of Context-Based Perpuz Learning Media to Support Periodic Table Learning - Rani Wulandari; Muhammad Zamhari (South Sulawesi Education Development (SSED), 2025)
Chemistry learning at the senior high school level tends to prioritize the mastery of theoretical concepts, often neglecting the practical application of chemistry in real-world contexts. This condition is reflected in the use of learning media that do not fully integrate theory with relevant real-world examples. Based on this urgency, this study aims to develop and validate context-based Perpuz learning media to support learning of the periodic table. This study employs the Research and Development (R&D) method, utilizing a development model that is limited to only three main stages of the 4D development model: define, design, and develop, without incorporating the disseminate stage. The data collection instruments used are validation sheets, product assessments, and student questionnaires. The validation results show that the learning media is declared to be highly valid because it has met the criteria and feasibility in various aspects, including: content, context, presentation, appearance, typography, media organization, language, and communication. The assessment by chemistry teacher reviewers has shown that the media obtained an overall score of 91%, indicating that it has been verified by learning practitioners and deemed feasible and practical for supporting the periodic table learning process. The results of the student response questionnaire suggest that the media aligns with student needs and has a high degree of uniqueness and appeal, as evidenced by an ideal percentage of 92%, characterized by high student enthusiasm during the learning process. Thus, this study has successfully developed innovative Periodic Puzzle learning media to support the learning process of the periodic table.